Peran Kepemimpinan dan Budaya Lokal dalam Penanganan COVID-19 di Provinsi Bali - Fatmah Fatmah (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
The increase in positive cases of COVID-19 in Indonesia since 2020 has led to various control measures, including prevention. One of them is through cultural approach and local wisdom that differs from one region to another, such as the one applied in Bali Province. The purpose of the study was to explore Bali’s experience in dealing with COVID-19 from the perspective of culture and local wisdom. A qualitative approach was used in this study using in-depth interviews with the Bali Provincial DisasterControl Office (Badan Penanggulangan Bencana Daerah, BPBD) and the Bali Provincial Health Office. Results of this study showed that the Bali Province has a strong religious approach, consisting of hupokara, which isthe faith in the Creator as disaster is believed to be a tremendous force that has to be managed through a ceremony called niskala, which giving offerings to God for health and safety of the people of Bali Province. The Balinese believe that the COVID-19 virus can be controlled with rituals and offerings. The presence of Pecalang as a traditional security unit looked up to and obeyed by the Balinese people also supports the successful management of COVID-19. The unique approach of Bali Province that is based on the local wisdom through mobilizing Traditional Villages, promoting custom-based cooperation through the formation of a task force at the Traditional Village level, and with good leadership from the Governorof Bali has led to successful COVID-19 control in Bali Province. Bali has learned from the COVID-19 pandemic that togetherness and mutual cooperation among people are needed to prevent the spread of COVID-19 inthe province.